Pictogramas y lectoescritura en niños de inicial II de la escuela “Dr. Reinaldo Espinosa” periodo académico 2023-2024 - Jiménez Jiménez, Rebeca Fernanda (2024)
The purpose of this research work is to investigate the correct use of pictograms as a main playful tool to strengthen good foundations and begin a good reading and writing process with children of initial educational level II. Its objective was to analyze the use of pictograms in the begining of Reading and Writing process initiation, and also the correct use of this tool in the teaching-learning process is a significant way in this preschool stage that will define the students learning development. The methodology used was based on scientific, analytical and synthetic methods, based on a qualitative approach of a descriptive nature with a documentary modality, investigated from empirical bases deploying ourselves to scientific criteria. The theoretical framework presented defines pictograms as a facilitator for oral and visual communication, affectively stimulating expression, managing to bring the child closer with firm and strengthened steps to the process of reading and writing. The results obtained demonstrate that applying pictograms as a playful strategy in the development of reading and writing is necessary, efficient and indispensable in children at the initial educational level, since it develops communication skills, improving and increasing their vocabulary, allowing the student to express themselves better and starting basis for the reading and writing initiation process in preschool students. It is concluded that the teachers of this school in which the research was carried out, do not use pictograms constantly and also omit the importance of this tool in the process of acquiring reading and writing skills, since they have difficulty relating the images with their meaning, identifying that one of the factors that obstructs the development of reading and writing is presented because the children when working with the pictogram tool that the teacher handles in the classroom, are very conventional and lack innovation in their presentation, this engages the children attention and interest, due to this fact, activities are recommended because the pictograms as the main axis, are presented with a change or an innovative plus, such as variation in their colors, these that are more vivid and bright, with variable textures in the cards, with a greater range of figures that can be related to their environment, turning this resource into a playful attraction of individual and group interaction that encourages in an effective way the child's interest to engage reading and writing skills. Keywords: Writing, literacy, reading, pictograms